2015
DOI: 10.1002/2015rg000479
|View full text |Cite
|
Sign up to set email alerts
|

A review of stemflow generation dynamics and stemflow‐environment interactions in forests and shrublands

Abstract: Many geoscientists now recognize stemflow as an important phenomenon which can exert considerable effects on the hydrology, biogeochemistry, and ecology of wooded ecosystems and shrublands. Despite the explosive growth of stemflow research, until this review there has been no comprehensive attempt to summarize and synthesize this literature since 2003. Topical areas of substantive new knowledge in stemflow research include the following: (1) the interrelationships among stemflow and meteorological conditions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
294
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(309 citation statements)
references
References 233 publications
(535 reference statements)
11
294
4
Order By: Relevance
“…The inclination of the main branches was various in all the shrubs, with a relatively wide range of insertion angles (46-64°, C. korshinskii; 48-70°, H. rhamnoides; Table 1). It is known that stemflow is enhanced when the plant structure is cone or funnel shaped, since vertically orientated branches with insertion angles greater than 45° measured above the horizontal promote water flow towards the trunk (Levia and Germer, 2015;Pypker et al, 2005). A funnel shape is indeed a prerequisite for high stemflow production but is not sufficient on its own because the position of the leaves and their orientation and size also affect stemflow (Nanko et al, 2006;Park and Cameron, 2008).…”
Section: Stemflow Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The inclination of the main branches was various in all the shrubs, with a relatively wide range of insertion angles (46-64°, C. korshinskii; 48-70°, H. rhamnoides; Table 1). It is known that stemflow is enhanced when the plant structure is cone or funnel shaped, since vertically orientated branches with insertion angles greater than 45° measured above the horizontal promote water flow towards the trunk (Levia and Germer, 2015;Pypker et al, 2005). A funnel shape is indeed a prerequisite for high stemflow production but is not sufficient on its own because the position of the leaves and their orientation and size also affect stemflow (Nanko et al, 2006;Park and Cameron, 2008).…”
Section: Stemflow Propertiesmentioning
confidence: 99%
“…Throughfall is usually the major understory rainfall flux with growing-season values often representing >70% of the incident rainfall. Levia and Germer (2015) found that stemflow values accounted for 3.5%, 11.3% and 19.0% of rainfall for tropical, temperate and semiarid regions, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, this study emphasizes the need of combining both biotic and abiotic factors to understand stemflow dynamics. Moreover, despite the underestimation of stemflow in most hydrological studies because it represents only a small percentage of incident rainfall (Levia and Frost, 2003;Levia and Germer, 2015), stemflow intensities, much greater for some moments than the intensity of rainfall, highlight the paramount role of stemflow as a hotspot of infiltration and soil water content dynamics.…”
Section: P a P E R A C C E P T E D P R E -P R I N T V E R S I O N Wmentioning
confidence: 99%
“…According to Voigt & Zwolinski (1964) the amount of water flowing down the tree stem depends more on bark properties than on meteorological conditions. It has been observed that trees with rough bark have a higher water storage capacity and generate a smaller stemflow than trees with smooth bark (Voigt 1960, Levia & Frost 2003, Levia & Germer 2015. Van Stan et al (2015) used a LaserBark to compute bark microrelief, ridge-to-furrow amplitude and slope metrics for Fagus sylvatica L. and Quercus robur L. They observed that a smaller ridge-to-furrow amplitude and slope for Fagus sylvatica significantly lowered the bark water storage capacity, which strongly correlated to maximum funneling ratios and permitted stemflow generation at lower rain magnitudes, while larger ridge-to-furrow amplitude and slope values for Quercus robur reduce funneling, diminishing stemflow drainage for larger storms.…”
Section: Introductionmentioning
confidence: 99%